2022
DOI: 10.1017/jfm.2022.206
|View full text |Cite
|
Sign up to set email alerts
|

Non-homogeneous analysis of rogue wave probability evolution over a shoal

Abstract: Non-equilibrium evolution of wave fields, as occurring over sudden bathymetry variations, can produce rogue seas with anomalous wave statistics. We handle this process by modifying the Rayleigh distribution through the energetics of second-order theory and a non-homogeneous reformulation of the Khintchine theorem. The resulting probability model reproduces the enhanced tail of the probability distribution of unidirectional wave tank experiments. It also describes why the peak of rogue wave probability appears … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 87 publications
5
45
0
Order By: Relevance
“…The saturation depth has been indicated (without defining a terminology) in the theoretical work of Mendes et al. (2022), where those authors consider the enhancement of and takes place for . Yet, such a saturation depth has never been reported in experimental works.…”
Section: Results and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The saturation depth has been indicated (without defining a terminology) in the theoretical work of Mendes et al. (2022), where those authors consider the enhancement of and takes place for . Yet, such a saturation depth has never been reported in experimental works.…”
Section: Results and Analysismentioning
confidence: 99%
“…2021 a , c ), or by the stochastic model for non-homogeneous processes introduced in Mendes et al. (2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the homogeneity of surface waves is often assumed [27], whereas the relaxation of this condition is expected to play a role in rogue wave formation over a shoal [28]. Indeed, we recently provided a third framework [29] by taking nonhomogeneity into account. These three frameworks are complementary, because they rely on different physical approaches, respectively: Fluid dynamics analysis of wave harmonics, the statistical mechanics of water waves, and the lifting of long-held implicit assumptions regarding the homogeneity of ocean waves.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, spectrum bandwidth seems to have different types of effects in extreme wave distribution depending on whether they are in deep [25][26][27][28] or shallow water 13 . Furthermore, ocean processes such as shoaling or wave-current systems that drive wave trains out of equilibrium have been experimentally 22,25,[29][30][31][32][33][34][35][36][37] associated with increasing the occurrence of extreme waves by order of magnitude. However, it has been recently found that no established theoretical distribution to date, neither universal as Gumbel nor based on physical principles, can describe extreme wave statistics in a wide range of conditions .…”
mentioning
confidence: 99%